The role of mobile applications and online platforms in the rehabilitation process of patients with coronary heart disease: a literature review - Larysa Bielecka; Klaudia Bielecka (Kazimierz Wielki University, 2024)
Introduction Nowadays, diseases of the circulatory system, such as coronary heart disease, are among the leading causes of death worldwide. Cardiac rehabilitation, a complex, interdisciplinary intervention, aims to improve cardiovascular function, enhance quality of life, and reduce mortality risk. In the era of mobile technology development, mobile applications and online platforms supporting cardiac rehabilitation are gaining increasing importance.    Aim of the study The aim of this study is to review the literature on the effectiveness of digital tools as support mechanisms in the rehabilitation of patients with coronary heart disease, and to compare their effectiveness with traditional medical care.   Materials and Methods A review of randomized clinical trials (RCTs) published in 2024 regarding the use of mobile and online applications in cardiac rehabilitation was conducted. Five studies meeting specific selection criteria were identified.   Results Research shows that mobile applications and online platforms effectively support the rehabilitation of patients with coronary artery disease, achieving results comparable to or better than traditional care. Programs such as RehaPlus+ and mHealth improve physical activity, mental resilience, quality of life, and reduce stress and anxiety. Users of applications such as eMOTIVA and MCARE achieve better results in terms of diet, physical activity, and general well-being. These interventions also promote regular communication with the therapist, which supports the individualization of rehabilitation.   Conclusions Rehabilitation of patients with coronary heart disease using mobile applications or online platforms is equally effective as, or more effective than, standard medical care.